Short Term Hydro Thermal Scheduling using Lambda Gamma Iteration Method - Yadav, Deepika; Naresh, R.; Sarda, V.K.; Sharma, Veena; Goel, Paras Mani (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Abstract: Short term hydrothermal scheduling (STHTS) is a daily planning proposition in power system operation. The main purpose of hydro thermal generation scheduling is to minimize the overall operation cost and to satisfy the given constraints by optimally scheduling the power outputs of all hydro and thermal units under study periods, given electrical load and limited water resource. This paper presents the lambda-gamma iteration method for fixed head hydro-thermal problems. Also, hydro power input-output model with constant head has been developed for Sewa Hydro Electric Power Plant by using the curve fitting techniques by least square method in MATLAB 7.9 version software. From scheduling results, operational decisions can be made for the best performance under changing conditions of load, head, unit availability and other important constraints. Furthermore, these decisions may be used as an effective input to the on-line decision support system for real-time operation of reservoir systems in availability based tariff (ABT) context that results in increased power production and enhanced revenue earnings in the process of planning and management of a water resources project. DOI: http://dx.doi.org/10.3126/hn.v9i0.7068 Hydro Nepal Vol.9 July 2011 20-26